Parimutuel contests with strategic risk-sensitive bettors. Issue 12 (8th March 2016) - Geertsema, Paul; Schumacher, Christoph Rainer
ABSTRACT: Existing models in the parimutuel betting literature typically explain betting data by either assuming a single, representative bettor with certain risk preferences or by assuming that a number of risk neutral bettors compete strategically within a game theoretic framework. We construct a theoretical framework of parimutuel markets in which we model both strategic interaction and individual bettor risk preferences, distinguishing between sophisticated insiders and recreational outsiders. We solve this model analytically for the optimal insider betting amount in a static symmetric Nash equilibrium. A new data set of 126 million individual horse race bets in New Zealand from 2006 to 2014 allows us to calibrate the model. We find that insiders (those betting 100 or more) outperform outsiders by 7.5% in terms of realized returns. The best fit of the model to the data is obtained when insiders are assumed to be risk neutral and to have an information advantage of 0.08 in probability terms. This finding provides empirical support for the common assumption of risk neutrality in strategic interaction models of parimutuel betting.